Asuhan Keperawatan Pada pasien Dengan Rematik Di Wilayah Kerja Puskesmas Tanjung Baru Kabupaten Tanah Datar. - Lutfi Novrian; Sandra Dewi; Armaita Armaita; Hasmita Hasmita (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Rheumatism is one of the most common musculoskeletal disorders among older adults and can reduce physical function and quality of life. According to the World Health Organization (WHO), approximately 20% of the world's population suffers from rheumatism, with 5–10% occurring in individuals aged over 60 years. This study aimed to describe gerontic nursing care for an elderly patient with rheumatism in the working area of Tanjung Baru Public Health Center, Tanah Datar Regency. This study used a descriptive case study approach involving one client. Data were collected through interviews, observation, physical examination, and documentation using the nursing process from February 20–24, 2026. The assessment revealed complaints of chronic pain and joint stiffness in the knee and ankle that interfered with daily activities. Nursing diagnoses included chronic pain, impaired physical mobility, and risk for injury. Nursing interventions focused on pain management, mobility support, and injury prevention. After five days of nursing care, the client experienced decreased pain intensity, improved physical mobility, and better understanding of self-care management. Comprehensive nursing care was effective in improving the client’s health status and independence in managing rheumatism.